Moho density contrast in Antarctica determined by satellite gravity and seismic models - Abrehdary, Majid; Sjöberg, Lars (Geophysical Journal International, 2021)
As recovering the crust-mantle/Moho density contrast (MDC) significantly depends on the properties of the Earth’s crust and upper mantle, varying from place to place, it is an oversimplification to define a constant standard value for it. It is especially challenging in Antarctica, where almost all the bedrock is covered with a thick layer of ice, and seismic data cannot provide a sufficient spatial resolution for geological and geophysical applications. As an alternative, we determine the MDC in Antarctica and its surrounding seas with a resolution of 1°x 1° by the Vening Meinesz-Moritz gravimetric-isostatic technique using the XGM2019e Earth Gravitational Model and Earth2014 topographic/bathymetric information along with CRUST1.0 and CRUST19 seismic crustal models. The numerical results show that our model, named HVMDC20, varies from 81 kg m-3 in the Pacific Antarctic mid-oceanic ridge to 579 kg m-3 in the Gamburtsev Mountain Range in the central continent with a general average of 403 kg m-3. To assess our computations, we compare our estimates with those of some other gravimetric as well as seismic models (KTH11, GEMMA12C, KTH15C and CRUST1.0), illustrating that our estimates agree fairly well with KTH15C and CRUST1.0 but rather poor with the other models. In addition, we compare the geological signatures with HVMDC20, showing how the main geological structures contribute to the MDC. Finally, we study the remaining glacial isostatic adjustment effect on gravity to figure out how much it affects the MDC recovery, yielding a correlation of the optimum spectral window (7< n <12) between XGM2019e and W12a GIA models of the order of ~0.6 contributing within a negligible ± 14 kg m-3 to the MDC. This study was supported by project no. 187/18 of the Swedish National Space Agency (SNSA)